Emotion regulation interacts with gambling motives to predict problem gambling among emerging adults. (July 2020) - Marchica, Loredana A.; Keough, Matthew T.; Montreuil, Tina C.; Derevensky, Jeffrey L.
Highlights: 15.2% and 8.1% of gamblers (18–27 years old) reported moderated and problem gambling levels. Difficulties with impulse, emotional awareness and clarity were significant predictors of PG. Among motives enhancement and coping motives uniquely predicted PG. Coping interacted with goal-directed behavior, awareness and clarity in predicting PG. Abstract: Background: It is presently estimated that as much as 10% of emerging adults are at risk for a gambling disorder. The consequences stemming from problematic gambling engagement include increased substance use, mental health disorders, suicidality, financial strain and legal issues. The present study explores whether deficits in specific dimensions of emotion regulation coupled with the motivation to escape negative emotions (i.e., coping motives) increases the likelihood of problem gambling severity, while controlling for variables such as gambling frequency, age, and sex. Methods: A sample of 919 emerging adult gamblers ( Mage = 21.16 years-old, SD = 2.90, 48.1% female) completed an online survey including an assessment of problematic engagement in gambling over the past year, gambling motivations, and difficulties in emotion regulation. In total, 15.2% and 8.1% of this sample were at moderate or high risk for gambling disorder. Results: A series of six moderation analyses revealed that the total models accounted for approximately 37–38% of the variance in problem gambling and that coping motives interacted with less difficulties engaging in goal-directed behavior, increased lack of emotional clarity, and increased lack of emotional awareness to create a toxic mixture for problem gambling. Conclusions: These findings reveal the importance of considering both psychological factors such as emotion regulation and motivational factors in understanding who is at greatest risk for gambling problems